A relação das produtoras de audiovisual com o mercado para captação de recursos e oferta de product placement e branded content - Cabo, Simone Terra (2018)
The present study deals with the commercial relations of the audiovisual producers with the market through the funding of incentive laws, Product Placement and Branded Content, from the methods of secondary analysis and qualitative research with semistructured interviews carried out with producers of audiovisual and market companies of the Rio / São Paulo axis, and exploring ways that can simultaneously better meet market expectations - facing the challenges that are present in contemporary advertising - and enhance the sustainability opportunities of producers. The results of the research indicate the need for an innovative and proactive stance in strategic management by the producers, and the expansion of opportunities for the audiovisual sector, if a synergistic movement is sought with the transformations of the Digital Age and market expectations